Visible light-induced direct α C–H functionalization of alcohols - Linbin Niu (Nature Portfolio, 2019)
Alcohols are very useful building blocks in organic synthesis, however C–H functionaliztion in presence of free –OH groups is highly challenging. Here, the authors report a selective visible light-promoted α-functionalization of free alcohols with heteroarenes mediated by Selectofluor.